Targeting inflammation in non-small cell lung cancer through drug repurposing - Rajasegaran, Thiviyadarshini; How, Chee Wun; Saud, Anoosha; Ali, Azhar; Lim, Jonathan Chee Woei (Multidisciplinary Digital Publishing Institute, 2023)
Lung cancer is the most common cause of cancer-related deaths. Lung cancers can be classified as small-cell (SCLC) or non-small cell (NSCLC). About 84% of all lung cancers are NSCLC and about 16% are SCLC. For the past few years, there have been a lot of new advances in the management of NSCLC in terms of screening, diagnosis and treatment. Unfortunately, most of the NSCLCs are resistant to current treatments and eventually progress to advanced stages. In this perspective, we discuss some of the drugs that can be repurposed to specifically target the inflammatory pathway of NSCLC utilizing its well-defined inflammatory tumor microenvironment. Continuous inflammatory conditions are responsible to induce DNA damage and enhance cell division rate in lung tissues. There are existing anti-inflammatory drugs which were found suitable for repurposing in non-small cell lung carcinoma (NSCLC) treatment and drug modification for delivery via inhalation. Repurposing anti-inflammatory drugs and their delivery through the airway is a promising strategy to treat NSCLC. In this review, suitable drug candidates that can be repurposed to treat inflammation-mediated NSCLC will be comprehensively discussed together with their administration via inhalation from physico-chemical and nanocarrier perspectives.